Characterization of Specific Immune Responses of Mice Inoculated with Recombinant Vaccinia Virus Expressing an 18-Kilodalton Outer Membrane Protein of Brucella abortus - Vemulapalli, Ramesh (American Society for Microbiology, 2000)
Using the shuttle vector pMCO2 and the vaccinia virus wild-type WR strain, we constructed a recombinant virus expressing an 18-kDa outer membrane protein of Brucella abortus. BALB/c mice inoculated with this virus produced 18-kDa protein-specific antibodies, mostly of immunoglobulin G2a isotype, and in vitro stimulation of splenocytes from these mice with purified maltose binding protein–18-kDa protein fusion resulted in lymphocyte proliferation and gamma interferon production. However, these mice were not protected against a challenge with the virulent strain B. abortus 2308. Disruption of the 18-kDa protein's gene in vaccine strain B. abortus RB51 did not affect either the strain's protective capabilities or its in vivo attenuation characteristics. These observations suggest that the 18-kDa protein plays no role in protective immunity.